Examining the Challenges and Opportunities of Managing Public Services in a Complex and Interconnected World - Panini Karamchand (Journal of Public Representative and Society Provision, 2021)
This research looks into the difficulties and potentials of public service management in today's increasingly complicated and interconnected world. Through a review of the literature and an examination of the available data, the authors of this study highlight the obstacles that public administration must overcome in order to advance social, economic, and environmental sustainability. Multilateral cooperation, stakeholder engagement, strategic planning, public-private partnerships, innovation and entrepreneurship, sustainable development, community engagement, inclusive policies, social safety nets, renewable energy, sustainable land use, disaster risk reduction, digitalization of services, smart infrastructure, and cybersecurity are all identified as opportunities and potential solutions in the study. Managing public services in today's fast-paced world is fraught with complex challenges, and this analysis emphasizes the need for holistic approaches that involve cooperation and innovation across sectors. Policymakers and researchers working to promote social, economic, and environmental sustainability in the public sector can benefit from this study's suggestions and consequences.